Development of long-term primary cell culture of Macrobrachium rosenbergii: morphology, metabolic activity, and cell-cycle analysis - Sudarshan, Gurucharan; Weil, Simy; Manor, Rivka; Goldstein, Oron; Sultan, Eliya; Aflalo, Eliahu D.; Ofir, Rivka; Zimin, Sean V.; Rosental, Benyamin; Sagi, Amir (Frontiers in Marine Science, 2024)
This study details our efforts to establish a sustainable cell culture of Macrobrachium rosenbergii, involving a 90-day longitudinal study on embryonic primary cell culture. Daily monitoring revealed changes from singular diverse-sized cells attaching on days 4-10 to interconnected cell clusters, transitioning from 2D to combined 2D and 3D structures by days 7-10, leading to spheroid-like cell masses. Metabolic activity peaked at day 26, with proliferation and increased cell numbers retained up to date 40 before gradually declining. Cell-cycle analyses by FACS showed an inverse relationship between G0/G1 and S phases. Populations sorted on days 3 and 24 revealed eight seeded populations expressing proliferation markers MrMYC and MrPCNA, with six also expressing stem-cell markers MrOct-4 and MrSox-2/3. With increased cell density, metabolic activity, and reduced G0/G1 distribution towards S, it was hypothesized that splitting cultures at high-proliferating mitotic ratio peaks could enable successful passages. Indeed, two consecutive passages were achieved after 8 days and 4 days in culture. Cells post-passages expressed species-specific Mr18S, MrMYC, MrPCNA, MrOct-4, and MrSox-2/3. After decades of striving for a crustacean cell line, this study presents M. rosenbergii cultures comprising putative proliferating/stem-cell sub-populations. These mixed-population prawn embryonic cell cultures have the potential to serve as a foundational platform for immortalization, contributing to the longstanding goal of establishing sustainable cell-culture lines.